Pharmacological Targeting of the NLRP3 trLRR Domain with Isothiazolinones Overcomes CRID3-Resistant Inflammation - Woo, Hawon; Jang, Yeonseo; Kim, Soyeon; Kim, Wonyoung; Zhang, Fenfen; Mall, Raghvendra; Patel, Chirag N.; Kurera, Melan; Ngo, Chinh; Jiang, Simon H.; Nicotra, Asia; Py, Bénédicte F.; et al. (浪淘沙预印本平台, 2026)
The NLRP3 inflammasome is a key driver in inflammatory, infectious, metabolic, and neurodegenerative diseases. Although the NLRP3 inhibitor CRID3 (also known as MCC950) exhibits potent activity, it cannot inhibit several hyperactive NLRP3 mutations associated with autoinflammatory syndromes and has not progressed clinically, underscoring the need for the development of new NLRP3 inhibitors. Through a high-throughput screen, we identified LOC14, an isothiazolinone-containing small molecule, as a selective NLRP3 inhibitor. Distinct from CRID3, which targets the NACHT domain, LOC14 binds to or near the LRR domain of NLRP3 and inhibits both CRID3-responsive and CRID3-non-responsive hyperactive or gain-of-function NLRP3 variants. Furthermore, we identified that the carbonyl oxygen of the isothiazol-3(2H)-one moiety is critical for inhibitory activity. In mice, LOC14 exerted anti-inflammatory effects in skin inflammation, intestinal inflammation, and sepsis, demonstrating broad physiological and therapeutic relevance. Our findings highlight isothiazolinone-containing compounds as first-in-class NLRP3 inhibitors for use against inflammatory diseases.